2014
DOI: 10.1177/1479164114548027
|View full text |Cite
|
Sign up to set email alerts
|

The dual peroxisome proliferator-activated receptor alpha/delta agonist GFT505 exerts anti-diabetic effects in db/db mice without peroxisome proliferator-activated receptor gamma–associated adverse cardiac effects

Abstract: We report here the efficacy and safety of GFT505, a novel liver-targeted peroxisome proliferator-activated receptor alpha/delta (PPARα/δ) agonist, in the db/db mouse model of diabetes. Mice were treated with vehicle, GFT505, PPARγ agonist rosiglitazone or dual-PPARα/γ agonist aleglitazar for up to 8 weeks. All compounds comparably reduced fasting glycaemia and HbA1c and improved insulin sensitivity. The glucose-lowering effect of GFT505 was associated with decreased hepatic gluconeogenesis, correlating with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Studies in the db/db diabetic mouse showed GFT505 reduced fasting glucose and HbA1c and improved insulin sensitivity similar to the PPAR-g agonist rosiglitazone or dual-PPAR-a/-g agonist aleglitazar, but GFT505 did not have the adverse cardiac effects of the PPAR-g-activating drugs [70]. The absence of cardiac effects of GFT505 was confirmed in 12-month studies in cynomolgus monkeys [70].…”
Section: Gft505mentioning
confidence: 88%
See 1 more Smart Citation
“…Studies in the db/db diabetic mouse showed GFT505 reduced fasting glucose and HbA1c and improved insulin sensitivity similar to the PPAR-g agonist rosiglitazone or dual-PPAR-a/-g agonist aleglitazar, but GFT505 did not have the adverse cardiac effects of the PPAR-g-activating drugs [70]. The absence of cardiac effects of GFT505 was confirmed in 12-month studies in cynomolgus monkeys [70].…”
Section: Gft505mentioning
confidence: 88%
“…The liver-protective effects of GFT505 were demonstrated in various animal models of NAFLD/NASH and liver fibrosis including WD-fed hApoE2 KI transgenic mice and the benefits were shown to be partly related to PPAR-a effects and partly due to PPAR-a-independent mechanisms [69]. Studies in the db/db diabetic mouse showed GFT505 reduced fasting glucose and HbA1c and improved insulin sensitivity similar to the PPAR-g agonist rosiglitazone or dual-PPAR-a/-g agonist aleglitazar, but GFT505 did not have the adverse cardiac effects of the PPAR-g-activating drugs [70]. The absence of cardiac effects of GFT505 was confirmed in 12-month studies in cynomolgus monkeys [70].…”
Section: Gft505mentioning
confidence: 95%
“…Elafibranor (GFT-505) is a dual PPARα/δ agonist, aiming to combine the beneficial effects of activating the two receptors. Animal data demonstrate that a beneficial effect of elafibranor on serum triglycerides, cholesterol and high density lipoprotein (HDL), and a reduction in hepatic fat that is mediated, at least in part, by non-PPARα-dependent mechanism 22 23. Post hoc analysis of short-term (4–12 weeks) phase II clinical trials using elafibranor for the treatment of metabolic syndrome demonstrated a significant reduction in ALT in subjects in the top two quartiles at baseline22 24 and has shown an improvement in liver, adipose and peripheral tissue insulin sensitivity,24 making it a potentially attractive therapeutic agent for NASH.…”
Section: Medications With a Primary Metabolic Targetmentioning
confidence: 99%
“…There was, however, a higher incidence of hypoglycemia and muscle events in the aleglitazar group, and peripheral edema, although not heart failure [21]. The dual PPAR-a and PPAR-d agonist, GFT505, has promise for treating diabetes, lipids, and potentially NAFLD, with recent promising animal data [25,45]. Human data are also promising, with small clinical trials demonstrating triglyceride reduction of 16.7-21% in various patient populations with abdominal obesity, with no major safety concerns [23,24].…”
Section: Peroxisome Proliferator-activated Receptor Modulatorsmentioning
confidence: 95%